SUBJECT OF CRIMINAL INFLUENCE: ESSENCE AND CHARACTERISTICS OF INDIVIDUAL SIGNS (Bulletin of criminological association of Ukraine, 2024)
The article analyses the essence and individual characteristics of a special subject of crime - a subject of increased criminal influence. It is emphasized that currently there are lively scientific discussions on determining the essence of this category, assigning specific individuals to such a classification group, as well as identifying typical features of such individuals. Attention is drawn to the fact that the lack of clear definition of the content of this category creates a significant number of problematic issues during law enforcement, in particular regarding the exact qualification of the relevant criminal offense, as well as determining the system of circumstances that are subject to establishment and proof during the investigation of specific criminal proceedings. It is emphasized that this category of individuals has been studied in quite detail within criminology and forensics as leaders of the criminal environment, mainly in the context of studying the activities of criminal groups of various orientations. The existing scientific approaches to determining leaders of the criminal environment, as well as their classification according to the relevant features, are analysed. The typical characteristics of leaders of ethnic criminal groups proposed by scientists are studied. Special attention is paid to the analysis of authority as one of the key characteristics of the analysis of the subject of criminal influence, which actually determines the limits of its establishment and spread. The indicators by which the authority of such persons should be formed are highlighted. It is justified that in the context of the characteristics of the subject of criminal influence, it is necessary to focus on the total authority. The main parameters that characterize this type of authority are highlighted and their characteristics are given. The organizational abilities are analysed in detail as a component of the authority of the subject of criminal influence, as well as the place of the person in the informal classification of leaders of the criminal environment as a factor that determines the limits of the establishment and spread of criminal influence.
Keywords: criminal environment leader; criminal influence; authority; subject of criminal influence; «thief in law»